Model Manajemen Inovasi Pariwisata Berbasis Komunitas di Sumba Barat Daya untuk Mendukung Pencapaian SDGs - Karolus Wulla Rato; Katarina Yunita Riti; Gergorius Kopong Pati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyze the influence of community-based tourism innovation and community participation on tourism sustainability in Sumba Barat Daya, Indonesia. Employing a quantitative survey design, the research involved [number of respondents] local tourism actors. Data were analyzed using multiple linear regression to examine the effect of both independent variables on the dependent variable of tourism sustainability. The results reveal that both community-based tourism innovation and community participation have a positive and significant impact on tourism sustainability (R² = 0.586). Community-based tourism innovation emerges as the most dominant factor with a coefficient of 0.420 (p < 0.001), while community participation shows a coefficient of 0.315 (p < 0.001). These findings affirm that the development of sustainable tourism relies not only on the level of community participation but also on the capacity of local communities to innovate in managing tourism destinations. The novelty of this study lies in integrating the dimensions of innovation and participation within the context of community-based tourism in Eastern Indonesia, thereby enriching the literature on Community-Based Tourism (CBT) and providing a foundation for policymakers to formulate strategies for sustainable tourism development. The recommendations include strengthening community innovation capacity, enhancing participatory mechanisms, and fostering cross-sectoral synergy to support the achievement of the Sustainable Development Goals (SDGs), particularly SDG 1, SDG 8, SDG 11, and SDG 12.